THE DECISION OF CHOOSING A UNIVERSITY: THE IMPACT OF EDUCATION COSTS - Dedy Ansari Harahap; Dita Amanah; Muji Gunarto; Purwanto Purwanto (Universitas Putera Batam, 2021)
A Student Decision on Choosing a University: Impact of Education Costs. This study aims to analyze the effect of the cost of education on students' decisions to continue their studies in tertiary institutions. This study uses a quantitative approach with an explanatory research type. The research sample consisted of 380 respondents and statistically processed with the simple linear regression method using the SPSS version 26.0 application. The results showed that the cost of education had an effect on students' decision to choose a university. These findings indicate that higher education institutions must take into account the tuition fees charged to students. This is related to the level of students' ability to complete their studies at a college. Several studies have shown that in general the cost of education is important for universities to attract and retain students who are studying.